Opportunities and Barriers in Telerehabilitation for Coronary Bypass Patients: A Case Study from the Faroe Islands - Bertil Christian Pløen Sivertsson; Alex Voss Gartner; Tetsuya Takahashi; Pernille Heyckendorff Secher (Telemedicine Reports, 2025)
Introduction: Cardiovascular disease is a leading global cause of death, with coronary artery disease often requiring coronary artery bypass grafting (CABG). Inadequate rehabilitation increases health risks and costs, and low adherence to center-based rehabilitation has prompted interest in telerehabilitation. Despite technological advances, the global implementation of telerehabilitation for CABG patients remains underexplored. This study investigates factors influencing the implementation of a telerehabilitation device for CABG patients in the Faroe Islands. Materials and Methods: A qualitative case study design was used to identify factors influencing the b-near® system implementation at Suðuroy Hospital in the Faroe Islands. Data collection involved document materials, direct nonparticipant observations, and semi-structured interviews with seven participants. Analysis with NVivo followed principles by Kvale and Brinkmann and the Normalization Process Theory. Results: The case study identified both opportunities and barriers. At Suðuroy Hospital, the b-near system enhances training and communication between health care providers and patients, is easy for patients to manage, and eliminates the need for hospital transportation. However, barriers such as reduced social interaction and potential difficulties in understanding training audio were also revealed. Discussion: Several factors were identified, highlighting the importance of integrating these findings into Suðuroy Hospital’s implementation strategy. Overcoming barriers is crucial for the successful use of the b-near system and improved patient care. Further evaluation of the b-near system and similar devices in diverse health care settings is necessary to enhance patient outcomes and support broader implementation.